Education on Tolerance Development: A Case Study - C. Katansky; I. Emilov (University of Sofia, 2009)
The article presents the most important results of a study, based on a concrete practice - an international project, titled "Teaching Tolerance". This project has been carried out by partner institutions from Germany, Bulgaria, Turkey and some other countries as a part of the biggest European Community "Lifelong Learning (LLL) Programme". The project ended successfully in 2008 but the LLL program is providing wide facilities for development of future teaching tolerance projects. From this aspect, the experience which was conducted will be beneficial for universities, schools, and other educational and cultural organizations which can develop projects or participate as partners in them.